Sustainability and Public Policy for Contaminants in Brazil (Research, Society and Development, 2018)
The purpose of this article is to briefly explain the impact of new legislation on agricultural and road machinery (MAR-1) on the scope of the consumer. To do so, it will investigate methodologically the new legislation, in which products it will impact and how it will affect the consumer and the population in Brazil as a whole. It also provides a didactic summary of the main differences between currently used diesel fuel and its successor. After referring to this object theoretically, it is presented as a result that, clearly, there is a lack of social involvement between the industry and academic area in the search to clarify to the different public the understanding of the trivial need of coverage of the emissions controls in the country and, as a conclusion , it is inferred that the legislation will be a great opportunity for Brazil to cover all areas related to the subject and the main beneficiary will be the society of the country.